Spatially featured porous chitosan conduits with micropatterned inner wall and seamless sidewall for bridging peripheral nerve regeneration. (15th August 2018) - Li, Guicai; Xue, Chengbin; Wang, Hongkui; Yang, Xiaoming; Zhao, Yinxin; Zhang, Luzhong; Yang, Yumin
Highlights: Chitosan conduit with inwall micropatterning while sidewall seamless was fabricated. Conduits size including diameter and length could be conveniently varied. The prepared chitosan conduits could well promote peripheral nerve regeneration. The conduit has potential application for nerve and other tissue regeneration. Abstract: In this study, a facile process for efficient and scalable fabrication of biomaterials conduits with seamless sidewall and longitudinally aligned structure on luminal inwall by combining use of lyophilization and micromolding method was firstly developed and reported. The micropatterned chitosan conduits possessed better mechanical matching with the normal sciatic nerve. The highly aligned microstructure could accelerate the orientation growth of newborn tissue, whereas the porous sidewall is anticipated to be beneficial for loading biofactors and reducing nutrition leakage or neurite exogenesis. The as prepared chitosan conduits with micropatterned inwall are proven to significantly promote the regeneration of 10 mm-gapped sciatic nerve of rat. Taken together, the study provides an important experiment and application basis for design and development of new generation of artificial implants for peripheral nerve regeneration, which may also substantially extend current knowledge concerning the engineered biomaterials conduits for tissue engineering and regenerative medicine.